2007
DOI: 10.1088/0953-8984/19/14/145201
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of resonating valence bond physics in spin–orbital models

Abstract: Abstract. We discuss how orbital degeneracy, which is usually removed by a cooperative Jahn-Teller distortion, could under appropriate circumstances lead rather to a Resonating Valence Bond spin-orbital liquid. The key points are: i) The tendency to form spin-orbital dimers, a tendency already identified in several cases; ii) The mapping onto Quantum Dimer Models, which have been shown to possess Resonating Valence Bond phases on the triangular lattice. How this program can be implemented is explained in some … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In particular, compass models appear in effective low energy description of quantum magnets that have a chiral degree of freedom (Budnik and Auerbach, 2004;Capponi et al, 2004;Ferrero et al, 2003;Mila et al, 2007). In these systems, the degree of freedom plays the role of the pseudo-spin with non-trivial directional dependence of the coupling.…”
Section: Chiral Degrees Of Freedom In Frustrated Magnetsmentioning
confidence: 99%
“…In particular, compass models appear in effective low energy description of quantum magnets that have a chiral degree of freedom (Budnik and Auerbach, 2004;Capponi et al, 2004;Ferrero et al, 2003;Mila et al, 2007). In these systems, the degree of freedom plays the role of the pseudo-spin with non-trivial directional dependence of the coupling.…”
Section: Chiral Degrees Of Freedom In Frustrated Magnetsmentioning
confidence: 99%
“…Perovskite-type 6H-Ba 3 CuSb 2 O 9 is a good candidate material for the spin-orbital liquid state that has been theoretically proposed (9)(10)(11). Recently, we reported that spin-orbital short-range ordering occurs in the short-range honeycomb lattice of Cu 2+ with e g orbital degrees of freedom, as depicted in Fig.…”
mentioning
confidence: 96%
“…The orbital degree of freedom also has an intrinsic frustration effect even without geometrical frustration; all bond energies in a certain orbitally ordered state cannot be minimized simultaneously. From these points of view, the QSL states in magnets with the orbital degeneracy, as well as the spin-orbital quantum liquid states, have been proposed theoretically [8][9][10][11][12], and candidate materials, such as LiNiO 2 and FeSc 2 S 4 , have been examined experimentally [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The QDM is also applicable to the quantum magnets with orbitally degeneracy. A description of the resonant spin-orbital dimers was attempted in a triangular lattice system motivated from the experiments in LiNiO 2 [11]. A spin-orbital system in a honeycomb lattice is another candidate, in which the spin-dimer picture gives an appropriate description for the ground state.…”
Section: Introductionmentioning
confidence: 99%